Clinical Evidence for treating chronic lateral epicondylitis with ozone (Ozone Therapy Global Journal, 2021)
Objective: Chronic lateral epicondylitis, also known as tennis elbow, is a common cause of elbow pain and dysfunction. It is generally believed to be due to a strain of the common extensor origin, but fibrosis and micro-tearing in extensor carpi radialis brevis are also possible. In acute conditions, a period of rest and or modification of activity may allow the condition to settle. Controversy exists regarding the best treatment strategy for chronic lateral epicondylitis. NSAIDs, Physical therapy, bracing, injections with corticosteroids, and more recently biologics are among the mainstream treatments. The use of ozone therapy in pathologies of the musculoskeletal system has been well documented. Is it possible that ozone could offer a better solution to the management of patients suffering from chronic lateral epicondylitis? The purpose of this paper is to review the evidence. Method: Through an online search of PubMed and ISCO3 databases two studies which included the use of ozone in patients with chronic lateral epicondylitis were found. One retrospective cohort study performed with 89 patients compared effects of ozone injection to extracorporeal shockwave therapy on management of pain. Another retrospective study with 80 patients compared ozone injection to corticosteroid injection and alleviation of pain. Conclusion: Results of available studies on the effect of ozone in treatment of chronic lateral epicondylitis demonstrate a superior action of ozone for the long-term elimination of pain when compared to corticosteroid injection and shockwave therapy.